The Influence of Business Capital, Digitization, and Access To Financing on The Performance of Culinary Micro, Small, And Medium Enterprises (MSMES) In Palembang - Farhanando; Sartika, Dewi (Indonesian Scientific Publication, 2026)
This study aims to examine how business capital, digitization, and access to financing influence the performance of culinary Micro, Small, and Medium Enterprises (MSMEs) in Palembang. A total of 100 respondents from local culinary MSMEs were surveyed. Data were analyzed using the Partial Least Squares (PLS) method through SmartPLS 3.0 software. The results indicate that business capital and access to financing have positive and significant effects on MSME performance, while digitization shows a positive but insignificant effect. These findings suggest that sufficient business capital and financing access are essential for improving MSME performance. However, digital adoption among MSMEs in Palembang remains suboptimal due to limited digital literacy and infrastructure. Strengthening capital and access to financing, alongside accelerating digital transformation, is necessary to enhance MSME competitiveness and sustainability.